Discovery and Characterization of the Key Constituents in Ginkgo biloba Leaf Extract With Potent Inhibitory Effects on Human UDP-Glucuronosyltransferase 1A1 - Pang, Hui-Lin; Zhu, Guang-Hao; Zhou, Qi-Hang; Ai, Chun-Zhi; Zhu, Ya-Di; Wang, Ping; Dou, Tong-Yi; Xia, Yang-Liu; Ma, Hong; Ge, Guang-Bo (Frontiers in Pharmacology, 2022)
Human UDP-glucuronosyltransferase 1A1 (hUGT1A1) is one of the most essential phase II enzymes in humans. Dysfunction or strong inhibition of hUGT1A1 may result in hyperbilirubinaemia and clinically relevant drug/herb-drug interactions (DDIs/HDIs). Recently, a high-throughput fluorescence-based assay was constructed by us to find the compounds/herbal extracts with strong inhibition against intracellular hUGT1A1. Following screening of over one hundred of herbal products, the extract of Ginkgo biloba leaves (GBL) displayed the most potent hUGT1A1 inhibition in HeLa-UGT1A1 cells (Hela cells overexpressed hUGT1A1). Further investigations demonstrated that four biflavones including bilobetin, isoginkgetin, sciadopitysin and ginkgetin, are key constituents responsible for hUGT1A1 inhibition in living cells. These biflavones potently inhibit hUGT1A1 in both human liver microsomes (HLM) and living cells, with the IC50 values ranging from 0.075 μM to 0.41 μM in living cells. Inhibition kinetic analyses and docking simulations suggested that four tested biflavonoids potently inhibit hUGT1A1-catalyzed NHPN-O-glucuronidation in HLM via a mixed inhibition manner, showing the Ki values ranging from 0.07 μM to 0.74 μM. Collectively, our findings uncover the key constituents in GBL responsible for hUGT1A1 inhibition and decipher their inhibitory mechanisms against hUGT1A1, which will be very helpful for guiding the rational use of GBL-related herbal products in clinical settings.